“Governance in the Protection of Immovable Property Rights in Albania: A Continuing Challenge” : A World Bank Issue Brief - Second Edition - World Bank (Washington, DC, 2013)
Despite several attempts at reform, immovable property rights in Albania are not adequately secure and represent an important governance challenge. Problems have resulted from incomplete first title registration, the lack of accurate cadastral records, and, in many cases, the absence of reliable evidence of ownership. Although Albania has adopted legislation calling for restitution or compensation for owners whose property was expropriated under communism, implementation is incomplete. In Albania, rapid internal migration has resulted in informal occupation of land and unauthorized construction on a mass scale, thus compounding the problems associated with the incomplete transfer of property. During the 1990s, as much as one-third of the population of some northern and mountainous regions migrated to urban, peri-urban, and coastal areas in search of income generation opportunities, despite the lack of adequate housing infrastructure or public service provision. Internal migration continues, albeit at a slower pace. Gaps in territorial planning legislation and administrative failures in the issuance of construction permits have made it difficult to obtain an appropriate construction permit, even when occupiers have legal title to the land. State authorities have largely failed to prevent new illegal occupation of land and illegal construction, and it is estimated that up to one-third of all buildings in Albania are illegal due to the occupier's lack of clear title and/or appropriate construction permit. This review of immovable property rights in Albania draws primarily upon this definition, which takes into account the popular legitimacy of state institutions and respect for the law among citizens and government institutions the softer aspects of governance that are essential to understanding how policies are made and implemented in practice and how public resources are used.